مفتاح اللغة العربية, طبعة ثانية - Usop, Mohd Puzhi; Mohamed Gameil Ali, Hussein; Mat Zain, Zairul; Wan Abdullah, Wan Najmuddin; Mustapai, Mohd Zulhisyam; Haggag, Hassan Sayed Hassan; Wan Abu Bakar, Wan Mohd Zahari; Abd Hamid, Mohd Azrul Azlen; Wan Husain, Wan Ahmad Rahiman (IIUM Press, International Islamic University Malaysia, 2019)
The aim of this book is to teach Arabic to non-native speakers, especially for beginners. Moreover, it is designed to give easy comprehension and understanding for students. The book is exposed to Arabic sounds and alphabets, dialogues and short reading texts. It focuses on the topics of daily life and simplifies religious and worldly or modern knowledge in the form of paragraphs on various topics such as the Holy Quran, Hadith, prayers (Doa), economy, arts, science, medicine and engineering. The book also offers some language structures to train students with a simple introduction to grammar. The book also contains moral values aimed at the formation of a good generation that helps to build the Islamic Ummah.